1999
DOI: 10.1089/104454999315556
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Binding of HLF/DBP Heterodimers Represents One Mechanism of PAR Protein Transactivation of the Factor VIII and Factor IX Genes

Abstract: The regulatory regions of the genes for coagulation Factors VIII and IX contain binding sites for both liver-enriched and ubiquitous transcriptional regulators. We investigated the role of the liver-enriched protein, hepatic leukemia factor (HLF), in mediating transcriptional regulation of the Factor VIII and IX genes. Using transient transfection assays in HepG2 hepatoma cells, we demonstrated the ability of HLF alone and in synergistic combination with the D-box binding protein (DBP), another proline and aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…Triple deletion of TEF, DBP and HLF in mice led to the impaired detoxification35 and lipid metabolism,36 whereas the specific role of HLF was missing. In addition, HLF was reported to be involved in viral replication23 and factor IX expression24 in HepG2 or Huh7 cancer cells. Nevertheless, the role of HLF in liver fibrosis remains unreported.…”
Section: Discussionmentioning
confidence: 99%
“…Triple deletion of TEF, DBP and HLF in mice led to the impaired detoxification35 and lipid metabolism,36 whereas the specific role of HLF was missing. In addition, HLF was reported to be involved in viral replication23 and factor IX expression24 in HepG2 or Huh7 cancer cells. Nevertheless, the role of HLF in liver fibrosis remains unreported.…”
Section: Discussionmentioning
confidence: 99%
“…29,34,35 Because in many cases, such as in K562 and 293 cells as shown here, all 3 family members are present, the possibility exists for a number of different functional complexes. Begbie et al 36 have presented data demonstrating a synergistic effect on the transactivation of the factor VIII and factor IX genes by DBP and HLF. Although our data suggest both HLF and TEF may be functionally active, we have no evidence at this time for a similar synergistic or even additive effect by PAR proteins in the regulation of the LMO2 gene.…”
Section: Discussionmentioning
confidence: 99%
“…DBP was shown to be able to from heterodimers with other family members of the proline and acidic-rich (PAR) protein family like HLF (Begbie et al, 1999). In transient transfection assays with HepG2 cells, HLF alone and in synergistic combination with the DBP was able to transactivate the promoters of the blood coagulation factors factor VIII and factor IX.…”
Section: F D Site-binding Protein Forms Homo-and Heterodimers With Pmentioning
confidence: 99%
“…At least some of the synergistic activation of the factor VIII promoter seen with HLF and DBP cotransfection could be attributed to increased binding of HLF-DBP heterodimers to two factor VIII promoter sites. Several observations indicated that the PAR family of transcription factors plays an important and complex role in regulating expression of the factor VIII and factor IX genes, involving the binding of both homodimeric and heterodimeric complexes of HLF and DBP to several sites in the promoters (Begbie et al, 1999).…”
Section: F D Site-binding Protein Forms Homo-and Heterodimers With Pmentioning
confidence: 99%